Determining the refractive index dispersion and thickness of hot-pressed chalcogenide thin films from an improved Swanepoel method - Fang, Y.; Jayasuriya, D.; Furniss, D.; Tang, Z.Q.; Sojka, Ł.; Markos, C.; Sujecki, S.; Seddon, A.B.; Benson, T.M. (Springer, 2017)
The well-known method presented by Swanepoel can be used to determine the refractive index dispersion of thin films in the near-infrared region from wavelength values at maxima and minima, only, of the transmission interference fringes. In order to extend this method into the mid-infrared (MIR) spectral region (our measurements are over the wavelength range from 2 to 25 μm), the method is improved by using a two-term Sellmeier model instead of the Cauchy model as the dispersive equation. Chalcogenide thin films of nominal batch composition As40Se60 (atomic %) and Ge16As24Se15.5Te44.5 (atomic %) are prepared by a hot-pressing technique. The refractive index dispersion of the chalcogenide thin films is determined by the improved method with a standard deviation of less than 0.0027. The accuracy of the method is shown to be better than 0.4% at a wavelength of 3.1 μm by comparison with a benchmark refractive index value obtained from prism measurements on Ge16As24Se15.5Te44.5 material taken from the same batch.